ARCHITECTURAL PRINCIPLES OF SHRINES IN UZBEKISTAN - Usarov Jamoliddin Tolkinovich (Zeta Repository, 2023)
The article describes the architectural values of places of pilgrimage in Uzbekistan. In particular, it is possible to attract a large flow of visitors through the promotion of pilgrimage tourism, because the ancient cities of Uzbekistan are recognized as magnificent centers of the Islamic world. Over the centuries, this land has given mankind a galaxy of great scientists, philosophers, statesmen and Islamic theologians, whose names are inscribed in golden letters in the history of mankind.